KENDURI NASI TRADITION IN THE MONTH OF SHA'BAN: STUDY OF THE VALUE OF ISLAMIC EDUCATION IN MALAY CULTURE - Neng Sufia; Fajar Aswati; Jarir (PT. Jurnal Center Indonesia Publisher, 2025)
The Kenduri Nasi tradition, held during the month of Sha'ban, is a tangible manifestation of the acculturation between Malay culture and Islamic teachings. This tradition not only strengthens social bonds but also functions as a medium for internalizing Islamic educational values such as shukr (gratitude), ukhuwwah (brotherhood), and social awareness. Using a qualitative approach through a literature review, this study explores the embedded Islamic values within Kenduri Nasi and its role in preserving local cultural identity. The findings reveal that Kenduri Nasi serves as a contextual medium for transmitting religious values across generations through culturally rooted practices. This tradition exemplifies a positive syncretism between Islamic teachings and Malay customs, making it relevant for character education based on local wisdom. It also provides a meaningful model for integrating religious teachings into everyday life in a way that is both accessible and culturally sensitive.